Pengaruh Penyampaian Konten Dakwah Di Tiktok Terhadap Efektifitas Dakwah Salamtv - Albahroyni, Albahroyni; Sazali, Hasan; Khatibah, Khatibah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
This study illustrates how social media Tiktok affects the efficacy of salam da'wah television. This study employs a quantitative survey method. The questionnaire is disseminated online via a Google form. The population consists of followers of the salamtv Tiktok account. the research data were analyzed using regression analysis. The results showed 1) there was a positive and significant effect on the delivery of da'wah on Tiktok to the effectiveness of salamtv da'wah with a value contribution of 55.1% and each increase of 1 delivery value will add to the value of the effectiveness of da'wah by 0.846. 2) there is a positive and significant influence on the da'wah content on Tiktok on the effectiveness of the da'wah of Salamtv with a value contribution of 55.9% and each increase of 1 delivery value will increase the value of the effectiveness of the da'wah by 0.695. 3) there is a positive and significant influence on the delivery of da'wah content on Tiktok together on the effectiveness of the da'wah of Salamtv with a value contribution of 59.7% and each increase of 1 delivery value will add to the effectiveness of da'wah by 0.435 and 0.390